Additive manufacturing of composite structures for the restoration of bone tissue. Issue 2 (4th June 2019) - Geven, M A; Grijpma, D W
Abstract: Bone defects of critical size are still challenging to repair and significant effort has been put into the development of composite structures fabricated by additive manufacturing (AM) as bone restoring materials. The controlled and fully interconnected porosity is one of the features that makes AM especially attractive for the reconstruction of bone defects. However, developments over the past years have yielded additional valuable findings on the optimization of additive manufactured composites for their application in bone restoration. In this review we discuss different AM techniques that can be applied for composite fabrication. We demonstrate the important parameters for composites processing and aim to illustrate how AM has facilitated the development of improved structures for bone repair.